alarm
Ask a question for free
Other
Jada

Si 2(x+3) − x = 11 + 4(x−½)entonces x es igual a:​

answers: 1
Register to add an answer
Answer:

x = - 1

Solución:   2 ( x + 3 ) - x = 11 + 4 ( x - )

                  2x + 6 - x = 11 + 4x - 2

                  x + 6 = 11 + 4x - 2

                  x + 6 = 4x + 9

                  6 = 4x + 9 - x

                  6 = 3x + 9

                  6 - 9 = 3x

                  - 3 = 3x

                  - 1 = x

                    x = - 1

Espero haberte ayudado :)

175
Dianatus
For answers need to register.